Maternal Single Parent Family - Iancu, Laura (New Trends in Psychology, 2024)
Single parenthood following divorce often brings with it a decrease in the mother’s involvement in her children’s upbringing, as demonstrated in a study by Bawin-Legros. This is explained by the mother’s emotional overload. Single parenthood is slowly turning from a stigma into a common feature, from abnormal to normal. The most consistent argument in this regard is that more than a quarter of families in Romania are single-parent families. When families become single-parent families as a result of divorce or separation of parents, the ties between the child and the parent with whom he or she does not live permanently tend to break down in a very large number of cases.